Perspectivas para uma rearticulação entre filosofia e espiritualidade : mística e intuição em Bergson - Rochamonte, Catarina (Universidade Federal de São Carlos, 2016)
We defend in this work the possibility of rescue, by means of Henri Bergson work, the spiritual aspect of philosophy and offer a world vision to the comteporaneity higher, in our view, than a purely aesthetic and hedonistic perspective as celebrated in postmodernity. The path chosen for display of this thesis was initially an analysis of Bergson’s conception of intuition, showing the consequences of this notion in the critique of traditional metaphysics and in the construction of a new metaphysics of duration, followed by a study of Bergson's understanding of mysticism, as well as its crucial role in the moral and spiritual development of humanity. We defend, with Bergson, a creative evolution still ongoing, understanding the philosophical intuition as an effort that takes the intellect to its limits and mystical intuition as an effort that elevates an individual beyond himself. We also find the exceptionality of the mystique and the consequent need for reflections on the possibilities of indirect application of what the great mystics bequeathed to us.
Keywords: Bergson; Intuição; Metafísica; Espiritualidade; Mística; Mystique; Spirituality; Metaphysics; Intuition; CIENCIAS HUMANAS::FILOSOFIA::METAFISICA